Normatively defined requirements for the planning of social services in the national map in 2021 (Politics & Security, 2021)
The article presents the normatively defined requirements for the by the municipalities, it is necessary to prove the need for the planning of the respective social service on the basis of official data received from official bodies. Based on the analyzes, the Mayor of the Municipality makes a proposal to the Municipal Council for inclusion of the social service in the National Map.
Keywords: planning; social service; national map of social services; analyzes; proposals; municipality; municipal council; council on social issues